Psychological Dimensions of Pertiwi as a Trigger of Conflict in The Film Kejarlah Janji of Garin Nugroho - Sukma, Melati; Rahman, Abdul; Girsang, Nitasri Murawaty (Kirana Publisher (KNPub), 2024)
This research analyzes the psychological dimensions of the character Pertiwi in the film Kejarlah Janji by Garin Nugroho. The author's aim in conducting this research is to describe characters that can be seen from one of the three dimensions of character, namely psychological, which can trigger conflict. The theory applied in this research uses the theory of characterization, character and conflict, using direct and indirect methods in the film Kejarlah Janji, especially the character Pertiwi. The research method used is qualitative with a descriptive approach. The results of this research show that there are 10 scenes that can show the psychological dimension of Pertiwi as a trigger for conflict in the film Kerjarlah Janji. The conclusion of this research is that the psychology, character and conflict experienced by the character Pertiwi in the film Kejarlah Janji can produce results that can be seen from the character's firmness, wisdom and anger, which can cause problems for other characters as well as for themselves and the environment surroundings.